ATIM-26. INTERIM RESULTS OF THE EXTENSION PHASE OF A PHASE I/IIA TRIAL OF A THERAPEUTIC CMV VACCINE AGAINST RECURRENT GLIOBLASTOMA (GBM). (11th November 2019) - Wen, Patrick; Reardon, David; Lee, Eudocia; Iwamoto, Fabio; Anderson, David; Diaz-Mitoma, Francisco; Lassman, Andrew
Abstract: Cytomegalovirus (CMV) antigens have been reported in over 90% of GBM tumors. CD4 + and CD8 + T cells are most frequently directed against the gB and pp65 antigens, respectively, and are immunogenic targets in a CMV-based GBM vaccine. We have initiated a phase I/IIa clinical trial for patients with recurrent GBM using gB/pp65 enveloped virus-like particles (eVLPs) formulated with GM-CSF and administered intradermally. In phase I, eligible patients were age 18–70 with Karnofsky Performance Status at least 70, normal end-organ function, on stable or decreasing corticosteroids of at most 4mg dexamethasone (or equivalent), with recurrent GBM following any standard initial therapy and any number of recurrences of any size. Patients were vaccinated monthly until tumor progression, with immune-monitoring performed 2 weeks after each vaccination and MRI exams every 6 weeks. The primary endpoint was safety/tolerability and secondarily to assess immunogenicity. Three vaccine doses (0.4µg, 2µg, and 10µg pp65) were evaluated with 6 patients in each cohort, and the DSMB identified no DLTs or safety concerns with any of the doses. The highest 10µg dose was chosen for the Phase IIa extension phase of the trial based on stable disease (3 months or longer) observed in 3/6 patients, which correlated with vaccine-induced IFN-γ-secreting T cell responses against CMV. Enrollment in phase IIa of the trial, which is designed to explore initial potential efficacy signals in an additional 10 patients that receive the optimal 10µg dose of vaccine, is expected in June 2019 and includes the additional requirements of unifocal, measurable enhancing tumor 1–3 cm across at first recurrence and no prior immunotherapy. Patients will be vaccinated monthly until clinical progression. Tumor responses and associated immunological biomarkers will be presented, and are expected to include initial data for all 10 patients.